Green approach to synthesize, spectral investigation and biological applications of potentially active ternary schiff base copper(II) complexes. (2021) - Dinesh Karthik, A.; Shakila, D.; Geetha, K.; Muthuvel, I.
Abstract: In this paper, a novel series of 4 mononucleate copper(II) complexes were synthesize from nitrogen-oxygen donor contain ternary Schiff base via environmentally green chemistry technique. The ternary schiff base copper(II) complexes were ready as of tyrosine, isoluecine with 2, 4-dihydroxybenzaldehyde by grinding technique. 1, 10-Phenanthroline/thiourea as a co-ligand were utilised in co-appointment with the schiff base in equimolar proportion. The complex be charaterized by means of basic analysis, magnetic moment, conduction measurements, IR along with UV–Visible spectral investigations. The synthesized complexes are neutral. From the infra-red spectral information of complexes, the value of Δν (νasCOO - − νsCOO - ) is 177–220 cm −1 showing monodentate bringing together the carboxylate gathering. Experimental info established to facilitate the copper atom be co-ordinated to the ligand moiety, organizing toward the metal through oxygen and nitrogen present in the ligand as well as with co-ligand. Complexes 1–4 show a slectron spin resonance vary by g|| > g⊥ showing d(x 2 -y 2 ) 1 state recommends sq. pyramidal geometry. oxidation–reduction potential of complex erstwhile explored by cyclic voltammetry. The complexes show higher inhibitor action against DPPH radicals. The in-vitro antibacterial drug and antifungal examinations were in addition performed for the complexes and also the outcomes disclosed that the Cu(II) complexes were more and more powerful against all the microorganisms beneath analysis.